Isoconversional nonisothermal kinetic analysis of municipal solid waste, refuse‐derived fuel, and coal. Issue 10 (6th July 2020) - Azam, Mudassar; Ashraf, Asma; Jahromy, Saman Setoodeh; Raza, Waseem; Khalid, Hassan; Raza, Nadeem; Winter, Franz
Abstract: The thermal characteristics and kinetic behavior of various solid wastes, including refuse‐derived fuel (RDF) and municipal solid waste (MSW), were investigated as a potential renewable energy source, in comparison with low‐rank coal. The experimental data were obtained in nonisothermal conditions through TGA analysis at specific heating rates. In addition to thermal characteristics of solid fuels, four isoconversional (model‐free) kinetic methods: a: Kissinger‐Akahira‐Sunose (KAS), b: Flynn‐Wall‐Ozawa (FWO), c: Friedman, and d: Vyazovkin were applied to calculate activation energies. In case of solid wastes, it is possible to say that the trend of activation energies of all isoconversional methods remains almost same in the selected region of conversion (0.1‐0.6 and 0.7‐0.9). Whereas in case of coal, Friedman model exhibits lower and inconsistent values of activation energy than others selected isoconversional methods. The experimental and modeling results revealed that that solid wastes (RDF and MSW) can be promising alternative energy sources to encounter energy crisis and uncontrolled waste disposal issues. Abstract : In this work, the thermogravimetric analysis is carried out, following by application of model‐free methods to propose a set of the kinetic parameters for combustion of coal, MSW, and RDF, to provide fundamental information for optimization of combustion process. The finding of this research work might open perspectives for the utilization (combustion and cocombustion) of solid wastes as promising alternative energy source and will provide new road map for waste management policies.